Freedom of Speech and Social Interaction in the Post-Communist Balkans: A Call for Cultural Education / Sloboda govora i komunikacija u društvu u postkomunističkom Balkanu: Poziv za edukaciju - Boškailo, Esad (Pregled: časopis za društvena pitanja / Periodical for social issues, 2025)
In the former Yugoslavia, the communist era was marked by a relatively mild form of socialism compared to other Eastern Bloc countries. While life was more liberal under Tito’s leadership, there were undeniable restrictions, particularly on freedom of speech. Media was partially controlled, and criticism of public figures, government policies, or political movements was limited. Open expression, though not completely suppressed, was carefully monitored, creating a social environment where people became accustomed to self-censorship.